Ultrastructure of the lacrimal drainage system in health and disease: A major review - Ali, Mohammad Javed; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Purpose: To provide a systematic review of the literature on the ultrastructural findings of the lacrimal drainage system in healthy state and in few of the disorders studied so far. Methods: The authors performed a PubMed search of all articles published with reference to electron microscopic features of the lacrimal drainage pathways. Data captured include demographics, study techniques, scanning or transmission electron microscopic features, presumed or confirmed interpretations and their implications. Specific emphasis was laid on addressing the lacunae and potential directions for future research. Results: Ultrastructural studies have led to better understanding of the lacrimal drainage anatomy-physiology correlations. Cellular interactions between fibroblasts and lymphocytes could form a basis for pathogenesis of punctal stenosis. Ultrastructural characterization of peri-lacrimal cavernous bodies and changes in primary acquired nasolacrimal duct obstruction (PANDO) led to them being partly implicated in its etiopathogenesis. Electron microscopic characterization of the dacryolith core promises insights into their evolution. Ultrastructural tissue effects of mitomycin-C during a DCR surgery has provided potential evidence of its role in cases with high-risk of failure. Lacrimal stent biofilms are common but their clinical implications are currently uncertain. Conclusion: Ultrastructural exploration of lacrimal drainage system so far has been limited and sparsely explored. The list of unexplored areas is exhaustive. There is a need for the lacrimal Clinician-Scientist to make themselves familiar with techniques and interpretation of electron microscopy to advance the ultrastructural frontier of this science.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Lacrimal drainage; Lacrimal sac; Nasolacrimal duct; Scanning electron microscopy; SEM; Transmission electron microscopy; Ultrastructure